Plasma Treatment after NiSi-Based Ohmic Contact Formation on 4H-SiC to Enhance Adhesion of Subsequent Backside Metallization - Becker, Tom; Hellinger, Carsten; Fuchs, Alesa; Körfer, Julien; Rusch, Oleg (Solid State Phenomena, 2024)
To achieve low on-resistance in any vertical 4H-SiC semiconductor power device, it is essential to create a suitable ohmic contact on the corresponding n-doped SiC substrate. In particular after wafer thinning, a common technology to reduce substrate resistivity, laser annealing for ohmic contact formation on the wafer backside is the only option due to temperature sensitive materials (such as Titanium or Aluminum) on the partially or fully processed wafer frontside. In this work, to solve adhesion issues of the backside metallization, plasma treatments, as easy to integrate process steps, were examined. By stripping obstructive carbon layers, formed after ohmic contact laser annealing, and without damaging the wafer frontside, an enhanced adhesion of following metallization layers was achieved. Both O2- and H2-plasma processes were investigated and demonstrated significant improvements to the adhesion of metallization stacks on the wafer backside compared to untreated surfaces and without drawbacks in the ohmic contact quality.<br